2018
DOI: 10.1021/acs.jcim.7b00397
|View full text |Cite
|
Sign up to set email alerts
|

ATPbind: Accurate Protein–ATP Binding Site Prediction by Combining Sequence-Profiling and Structure-Based Comparisons

Abstract: Protein–ATP interactions are ubiquitous in a wide variety of biological processes. Correctly locating ATP binding sites from protein information is an important but challenging task for protein function annotation and drug discovery. However, there is no method that can optimally identify ATP binding sites for different proteins. In this study, we report a new composite predictor, ATPbind, for ATP binding sites by integrating the outputs of two template-based predictors (i.e., S-SITE and TM-SITE) and three dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 54 publications
0
52
0
1
Order By: Relevance
“…Since the first version of ccPDB (18) published in 2011, there has been enormous growth in the development of improved methods in the field of secondary structure prediction (9, 19–24), irregular secondary structure prediction (10, 25–28), protein–ligand interactions (7, 15, 16, 29), DNA/RNA–protein interactions (13, 30, 31), protein crystallization and propensity prediction (32–35), dihedral angle prediction (6, 36–38), surface accessibility prediction (39), Rotamer libraries (8) and others (40–43). These methods have been found to annotate protein structure and function in comparison to earlier methods.…”
Section: Methodsmentioning
confidence: 99%
“…Since the first version of ccPDB (18) published in 2011, there has been enormous growth in the development of improved methods in the field of secondary structure prediction (9, 19–24), irregular secondary structure prediction (10, 25–28), protein–ligand interactions (7, 15, 16, 29), DNA/RNA–protein interactions (13, 30, 31), protein crystallization and propensity prediction (32–35), dihedral angle prediction (6, 36–38), surface accessibility prediction (39), Rotamer libraries (8) and others (40–43). These methods have been found to annotate protein structure and function in comparison to earlier methods.…”
Section: Methodsmentioning
confidence: 99%
“…ATPbind [67] was used to predict Bsd ATP binding residues; informatics predictions were compared to the VRK1 ATP binding pocket described in [43]. embryos that expressed wild-type Bsd in the mesoderm showed improved muscle morphology;…”
Section: Bioinformatic and Statistical Analysismentioning
confidence: 99%
“…Later on, it was realized that all ligands are not the same, and there is a wide variation in the shape and size of binding pockets. Therefore, researchers started developing ligand-specific methods (Chauhan et al, 2009;Chauhan et al, 2010;Chen et al, 2012;Yu et al, 2013a;Hu et al, 2016;Hu et al, 2018), and it was observed that these ligand-specific methods performed better than generalized methods (Chen et al, 2012;Yu et al, 2013b;Hu et al, 2016). Comprehensive information on the software developed for protein-small molecule interaction is reviewed in a paper by .…”
Section: Introductionmentioning
confidence: 99%